1997
DOI: 10.1177/096032719701600503
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species involvement in ricin-induced thyroid toxicity in rat

Abstract: 1 Ricin is known to have diverse effects on the cells of different organs like liver, kidney, pancreas, intestines and parathyroid. 2 Acute decrease in serum thyroid hormone levels 24 h after ricin administration (1.5 μg/100 g) led us to suspect the toxic action of ricin on the thyroid. 3 We monitored the lipid peroxidation (LP) and anti oxidant status of the thyroid tissue to determine the role, if any, played by reactive oxygen species (ROS) in this pathology. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 11 publications
(3 reference statements)
0
5
0
Order By: Relevance
“…It has previously been reported that R. communis lectin generates elevated level of reactive oxygen species (ROS) and induces DNA fragmentation [ 48 , 49 ] which eventually up regulates p53 [ 50 ], the critical regulator of mitochondria mediated apoptosis. Upon over-expression, p53 induces up-regulation of pro-apoptotic protein “Bax” which in turn down regulates anti-apoptotic protein “Bcl-2”.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been reported that R. communis lectin generates elevated level of reactive oxygen species (ROS) and induces DNA fragmentation [ 48 , 49 ] which eventually up regulates p53 [ 50 ], the critical regulator of mitochondria mediated apoptosis. Upon over-expression, p53 induces up-regulation of pro-apoptotic protein “Bax” which in turn down regulates anti-apoptotic protein “Bcl-2”.…”
Section: Discussionmentioning
confidence: 99%
“…The toxin kills almost all eukaryotic cells via RTA, which causes inhibition of protein translation by deglycosylation, depurination, and therefore cleavage of the ribosomal RNA (12). Use of chemically modified intact ricin or RTA alone covalently linked to antibodies and other ligands as pharmaceutics in clinical trials, while promising, remains fraught with difficulties such as whole-body nonspecific cytotoxicity and the lesser understood phenomenon of vascular leakage (13)(14)(15). It is believed that the residual nonmodified ricin commonly found in preparations of both chemically blocked ricin and RTA conjugates is the major source of these side effects.…”
mentioning
confidence: 99%
“…results in hypoglycemia and hepatic injury, effects linked to an increased neutrophil and monocyte infiltration with a subsequent increase in inflammatory cytokine levels (26). Ricin may increase the multiple organ damage induced by inflammatory cytokines by affecting cellular antioxidant enzyme levels; ricin exposure reduces the activities of superoxide dismutase and glutathione peroxidase while increasing xanthine oxidase activity in both kidney and liver, resulting in increased lipid peroxidation products (27)(28)(29)(30), an effect observed in this study. Human airway cells exposed to ricin show a marked inflammatory response with activation of nuclear factor (NF)-κB and increased expression of cytokines such as TNF-α (31).…”
Section: Discussionmentioning
confidence: 60%